Metformin enhances anti-tumor effect of L-type amino acid transporter 1 (LAT1) inhibitor - Seiji Ueno; Toru Kimura; Takashi Yamaga; Akihiko Kawada; Toshiaki Ochiai; Hitoshi Endou; Hiroyuki Sakurai (Elsevier, 2016)
Background: In many cancer cells, L-type amino acid transporter 1 (LAT1) transports neutral amino acids with bulky side chain, which activate mammalian target of rapamycin (mTOR) to cause cell proliferation. An anti-diabetic drug, metformin, has been shown to activate AMP-activated protein kinase (AMPK), which leads to inhibition of mTOR. LAT1 inhibition in combination with metformin could result in more prominent suppression of mTOR activity. Purpose: Anti-proliferative effect of a newly developed LAT1 specific inhibitor JPH203 in combination with metformin is evaluated in 2 head and neck cancer cell lines, Ca9-22 and HEp-2 cells and in nude mice inoculated with Ca9-22 cells. Results and Discussion: By MTT assay, 0.5 mM metformin inhibited proliferation of Ca9-22 cells to 70% of control. In the presence of 100 μM JPH203, proliferation of Ca9-22 cells was inhibited to 60% of control. By combining these 2 drugs, proliferation of Ca9-22 was significantly inhibited to 40% of control. However, this regimen was not very effective against HEp-2 cells. This combination also suppressed in vivo growth of Ca9-22 cells in a xenotransplant model. A combination of anti-LAT1 drug with metformin may be an effective anti-proliferative therapy for certain subsets of cancers.